Discription on a new species of Elasmus westwood (Hymenoptera:Chalcidoidea) with notes on host-parasitic relationship of some Indian species - Prakash, Ved; Verma, Mahesh (International Multidisciplinary Research Journal, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif][if gte mso 9]> <![endif][if gte mso 10]> <![endif]–> A new Indian species of Elasmus in described in the sub family Elasminae Eulophidae from Bareilly district (U.P.), with a host parasite list of some species reared from plant hosts such as fig receptacles, fruits and galls. The parasites emerged from galls made by insects mostly belonged to family Encentidae, Aphelimidae, Eulopidae and Brachonidae. Host parasite list in compiled from the catalogue (Verma and Hayat, 1986).